Ostomy or intestinal anastomosis in cases of peritonitis - Rasslan, Samir (1995)
Twenty-six patients showing peritonitis due to nontraumatic acute abdomen were submitted to ostomy. Mean age was 51 years (range 25-83), being 13 males and 13 females. Bowel obstruction (BO) was the most frequent cause of peritonitis (11 cases), followed by intestinal perforation (IP) (8 cases), acute mesenteric infarction (AMI) (5 cases), and acute abdomen of inflammatory / infectious origin (AAIO) (2 cases). Brook's ileostomy was performed on 65% of the patients. Jejunostomy was performed only in 4 patients, leading to a bad evolution. Overall mortality was 54%. Primary ostomy or anastomosis in cases of peritonitis constitute a highly controversial theme. Indications and problems involving the intestinal exteriorization in emergency surgery urgency are herein discussed.